2017
DOI: 10.4172/1948-5956.1000474
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Tumor of Soft Tissues: A Case Report and Review of Literature

Abstract: Background: Primary giant cell tumor (GCT) of soft tissue (GCTST) is an extremely rare slow-growing entity bearing a high similarity to conventional bone TCG (GCTB). The term, malignant tumor of giant cells of soft tissues have been reserved for histologically high-grade lesions. Although the gold standard remains surgical carcinological resection, bisphosphonates are beginning to prove their benefit in the treatment of GCTST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although complete resection is the primary treatment for GCT-ST, other treatment options include bisphosphonates and Denosumab, a human monoclonal antibody directed against RANKL 18,19) . Some authors have also advocated their use for the treatment of GCT-ST 20,21) . A proper diagnosis of GCT-ST could provide an opportunity to receive these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although complete resection is the primary treatment for GCT-ST, other treatment options include bisphosphonates and Denosumab, a human monoclonal antibody directed against RANKL 18,19) . Some authors have also advocated their use for the treatment of GCT-ST 20,21) . A proper diagnosis of GCT-ST could provide an opportunity to receive these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that zoledronic acid treatment succeeded in controlling tumor growth. There are two case reports concerning the use of zoledronic acid in cases of unresectable GCTST [52,53]. Mokrani et al reported a case of primary GCTST of the elbow that was judged unresectable due to its intra-articular extension [52].…”
Section: Advanced/metastatic Diseasementioning
confidence: 99%
“…There are two case reports concerning the use of zoledronic acid in cases of unresectable GCTST [52,53]. Mokrani et al reported a case of primary GCTST of the elbow that was judged unresectable due to its intra-articular extension [52]. The patient received zoledronic acid injections for 8 months and had stable disease.…”
Section: Advanced/metastatic Diseasementioning
confidence: 99%
“…Histologically, GCS are commonly benign neoplasms that contain spindle and round shaped cells associated with osteoclast‐like multinucleated giant cells 7,8 . In addition, GCS tend to be locally aggressive, recurrent, but rarely metastatic 9 . The treatment of choice for GCS is surgery 10 .…”
Section: Introductionmentioning
confidence: 99%